Critical intersex - Holmes, Morgan (Ashgate, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Section: 1 vol. (XIV-257 p.) ; 24 cm.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes

Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis